2022
DOI: 10.3390/ijerph19042306
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Inorganic Salts in Municipal Solid Waste Incineration Fly Ash Using a Washing Ejector and Its Application for CO2 Capture

Abstract: This study investigated the effects of washing equipment for inorganic salts, such as NaCl, KCl, and CaClOH, to decontaminate municipal solid waste incineration fly ash (MSW-IFA). Based on the feature of hydrodynamic cavitation, the device developed in this study (referred to as a ‘washing ejector’) utilizes the cavitation bubbles. A washing ejector was analyzed under a range of conditions, employing as little water as possible. In hydrodynamic cavitation, the increase in fluid pressure with increasing static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Fly ashes are commonly characterized by a high content of easily leachable salts [31]. In the fly ash used for the experiment, a high content of easily soluble salt was found, corresponding to 5030 mg NaCl L −1 , which allows it to be classified into the third salinity group according to FAO [35]. The salinity of the fly ash implicated into the Podzols, determined 11 years after the establishment of the experiment, was low even at the level of their deposition [6].…”
Section: Properties Of Soilmentioning
confidence: 99%
“…Fly ashes are commonly characterized by a high content of easily leachable salts [31]. In the fly ash used for the experiment, a high content of easily soluble salt was found, corresponding to 5030 mg NaCl L −1 , which allows it to be classified into the third salinity group according to FAO [35]. The salinity of the fly ash implicated into the Podzols, determined 11 years after the establishment of the experiment, was low even at the level of their deposition [6].…”
Section: Properties Of Soilmentioning
confidence: 99%
“…13−15 Kim et al used cavitation bubbles for salt removal by the physical effect role. 16 In addition, CO 2 was used in MSWI fly ash stabilization as well, namely, accelerated carbonation, but it aimed mainly at heavy metal stabilization for ash landfill and carbon capture, usually with the liquid− solid ratio less than 0.5 mL/g, much lower than that for ash washing (2−20 mL/g). 17 Because CO 2 can promote the bottom ash washing and react with fly ash components, does CO 2 also promote fly ash washing?…”
Section: Introductionmentioning
confidence: 99%
“…Water washing is effective for soluble salts but not for insoluble salts, which mainly existed in bottom ash . Some studies efficiently removed Friedel’s salt by sulfuric acid washing effectively from bottom ash. , Impressively, not only sulfuric acid but also CO 2 promoted the removal fraction of chlorine in MSWI bottom ash from 51 to 95% for Friedel’s salt decomposition. , Moreover, some previous studies reported bubbling CO 2 into washing filtrate for a further removal of heavy metals, without discussion on chlorine removal from ash. Kim et al used cavitation bubbles for salt removal by the physical effect role . In addition, CO 2 was used in MSWI fly ash stabilization as well, namely, accelerated carbonation, but it aimed mainly at heavy metal stabilization for ash landfill and carbon capture, usually with the liquid–solid ratio less than 0.5 mL/g, much lower than that for ash washing (2–20 mL/g) .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 But another study suggested that the formation of CaClOH was related to the ratio of Ca and Cl, and CaClOH became the predominant phase for the mixture of 50% Ca(OH) 2 −50% CaCl 2 •2H 2 O. 23 The CaClOH in IFA has been used for mineral storage of CO 2 , 24,25 and the carbonization process could increase the stabilities of the heavy metals. 26−28 But for the dechlorination process of IFA utilization, the dissolving behaviors and thermal stability of CaClOH need more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that CaClOH was the intermediate product for the reaction of gaseous hydrogen chloride and calcium oxide or calcium hydroxide. , But another study suggested that the formation of CaClOH was related to the ratio of Ca and Cl, and CaClOH became the predominant phase for the mixture of 50% Ca­(OH) 2 –50% CaCl 2 ·2H 2 O . The CaClOH in IFA has been used for mineral storage of CO 2 , , and the carbonization process could increase the stabilities of the heavy metals. But for the dechlorination process of IFA utilization, the dissolving behaviors and thermal stability of CaClOH need more attention. It was reported that CaClOH was the only chloride that existed in IFA after washing, , but other studies showed that CaClOH disappeared in washed incineration fly ash (WIFA). , Furthermore, the transformation of CaClOH in thermal treatment was also not clear.…”
Section: Introductionmentioning
confidence: 99%